Entrepreneurial Climate and Entrepreneurial Competencies: The Way to Enhance MSMEs Performance - Yudha Prakasa; Yan Raka Putri (Jurnal Kewirausahaan dan Bisnis, 2020)
As Indonesia's original cultural heritage, Hand-Written Batik is one of the featured products for Micro, Small, and Medium Enterprises (MSMEs) in Central Java. However, the printed batik industry's presence impacted the decline in the market share of hand-written batik. The entrepreneurial climate and entrepreneurial competence are factors that are believed to increase the competitiveness of hand-written batik. This study aims to determine and explain the effect of entrepreneurial climate on business performance with entrepreneurial competence as an intervening variable. This research is explanatory research with a quantitative approach and involves as many as 138 MSMES owners at the center of Hand-Written Batik in Bayat District, Klaten Regency as respondents. Withdrawal of samples using the Slovin formula with a confidence level of 95 percent. The sampling technique uses proportional random sampling, and data collection is done by distributing questionnaires to respondents. Data analysis using descriptive analysis and path analysis were processed using SPSS software. The results show that the entrepreneurial climate has a positive and significant influence on entrepreneurial competence, the entrepreneurial climate has a positive and significant effect on business performance, entrepreneurial competence has a positive and significant effect on business performance, and entrepreneurial competence is proven to be able to mediate the relationship between entrepreneurial climate and business performance. This means that the better the entrepreneurial climate in an MSMEs industrial center will impact MSMEs' performance if, at the same time, MSMEs owners have good entrepreneurial competence.Keywords: business performance, entrepreneurial climate, entrepreneurial competence, MSMEs